A preliminary research: The use of e-learning platforms by married women in Indonesia - Ridha Hidayani; Bunga Claudya (Inovasi Kurikulum, 2025)
Being a married woman comes with unique challenges, especially when it comes to self-empowerment. However, the rapid development of technology today has made it easier for individuals to access learning resources from anywhere, without needing to be physically present in specific locations. This creates a great opportunity for married women to utilize technology as a tool for personal growth through e-learning. This research aims to explore the e-learning platforms commonly used by Indonesian married women and assess the level of difficulty they face while learning. The study collected data from 100 married women across Indonesia using a quantitative survey method. The results showed that the five most popular e-learning platforms among respondents are Karier.mu, MySkill, Ibu Punya Mimpi, Habis Kerja, and Dibimbing.id. Furthermore, the survey revealed that 87 percent of married women find it challenging to learn and develop themselves after marriage, while only 13 percent reported that it was not overly difficult. These findings highlight the need for more accessible and supportive e-learning initiatives tailored to the unique circumstances of married women.   Abstrak teknologi saat ini memudahkan semua individu untuk mengakses sumber belajar tanpa perlu hadir di ruangan tertentu. Hal ini menjadi peluang besar bagi para perempuan yang sudah menikah untuk menjadikan perkembangan teknologi ini sebagai momentum dalam peningkatan pemberdayaan diri melalui e-learning. Tujuan dari penelitian ini adalah untuk mengetahui e-learning platform apa saja yang digunakan oleh para perempuan Indonesia yang sudah menikah serta mengetahui persentase tingkat kesulitan untuk belajar bagi seorang perempuan yang sudah menikah. Metode penelitian yang digunakan adalah metode kuantitatif. Metode kuantitatif yang digunakan yaitu metode survei. Survei dilakukan pada 100 perempuan yang sudah menikah di Indonesia. Berdasarkan hasil penelitian diperoleh informasi e-learning platform yang sering digunakan, lima besar diantaranya yaitu karier.mu, myskill, ibu punya mimpi, habis kerja, dibimbing.id. Adapun persentase tingkat kesulitan belajar dan mengembangan diri setelah menjadi perempuan yang sudah menikah yaitu sebesar 87 persen menyatakan sulit sedangkan 13 persen menyatakan tidak terlalu sulit. Kata Kunci: E-learning; pengembangan diri; perempuan